A 3D well-matched electrode pair of Ni–Co–S//Ni–Co–P nanoarrays grown on nickel foam as a high-performance electrocatalyst for water splitting. Issue 26 (15th June 2018) - Gong, Yaqiong; Xu, Zhoufeng; Pan, Hailong; Lin, Yu; Yang, Zhi; Wang, Jinlei
Abstract : The as-obtained Ni–Co–S//Ni–Co–P electrode pair can serve as a high-performance electrocatalyst for water splitting under electrochemical reaction conditions. Abstract : Seeking out new methodologies to assemble low-cost, highly efficient and stable oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) electrocatalysts continues to be a great impetus and significant challenge for designing renewable energy systems. In this paper, brush-like Ni–Co–M (M = O, S, Se and P) samples on three-dimensional (3D) hierarchically porous nickel foams (NF) were synthesized via thermolysis, sulfuration, selenylation and phosphorization, respectively, of the Ni–Co–precursor under an Ar atmosphere. Ni–Co–S/NF demonstrated an overpotential of 270 mV@40 mA cm −2 toward the OER and Ni–Co–P/NF demonstrated one of 156 mV@10 mA cm −2 toward the HER in 1.0 M KOH electrolyte. What's more, considering the beneficial superior activity of Ni–Co–S/NF for the OER and Ni–Co–P/NF for the HER, an electrode pairing of Ni–Co–SOER //Ni–Co–PHER was assembled for overall water splitting and the result was that only 1.57 V was needed to afford a current density of 20 mA cm −2 . Ni–Co–S//Ni–Co–P also demonstrated long-term durability during a 20 h stability test without obvious deactivation in 1.0 M KOH. The novelty of choosing the highest activity catalyst for the OER and HER from Ni–Co–M (M = O, S, Se and P) to construct a well-matched electrode pair and thus enhance the overall water splitting performance presents a wide range of possibilities for the further development of earth-abundant and highly efficient electrode pairs.